Innovative therapeutic strategies using ADHD medications tailored to the behavioral characteristics of patients with chronic pain - Kasahara, Satoshi; Takahashi, Miwako; Suto, Takashi; Morita, Taito; Obata, Hideaki; Niwa, Shin-Ichi (Frontiers in Pharmacology, 2025)
Chronic pain affects a significant portion of adults and is linked to psychosocial issues, cognitive dysfunction, and psychiatric disorders, complicating treatment. Attention deficit hyperactivity disorder (ADHD) is increasingly recognized as a contributing factor to chronic pain, particularly nociplastic pain, with a notable prevalence of comorbidity between ADHD and conditions like fibromyalgia and chronic low back pain. ADHD behaviors such as impulsivity and overactivity can exacerbate pain by leading patients to seek risky treatments or discontinue care prematurely. ADHD medications are expected to alleviate pain severity by improving associated cognitive dysfunction and addressing central sensitization, a fundamental mechanism in chronic pain. Brain abnormalities in ADHD contribute to increased spontaneous activity in the anterior cingulate cortex-posterior insular pathway due to neuroinflammation, alterations in action potential firing, and changes in transmission pathways in the spinal dorsal horn. Additionally, increased norepinephrine synthesis and reduced transmission efficiency amplify nociceptive information from the periphery and facilitate central sensitization in ADHD. Beyond typical ADHD medications like central stimulants, norepinephrine reuptake inhibitors, and alpha-2 receptor agonists, various antidepressants, mood stabilizers, antipsychotics, Parkinson’s disease medications, and antidementia medications have proven effective in alleviating ADHD symptoms. These medications, effective for ADHD, may offer innovative solutions for managing chronic pain by targeting both the cognitive/behavioral dysfunction and central sensitization observed in chronic pain comorbid with ADHD. Further research into these mechanisms could lead to new, more effective pharmacological treatments for chronic pain with comorbid ADHD, a condition that is often overlooked.